2014
DOI: 10.5194/bg-11-5411-2014
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effects of clear-cutting and strip-cutting on nitrate dynamics in a forested watershed using triple oxygen isotopes as tracers

Abstract: Abstract. Temporal variations in the stable isotopic compositions of nitrate dissolved in stream water eluted from a cool-temperate forested watershed (8 ha) were measured to quantify the biogeochemical effects of clear-cutting of trees and subsequent strip-cutting of the understory vegetation, dwarf bamboo (Sasa senanensis), with special emphasis on changes in the fate of atmospheric nitrate that had been deposited onto the watershed based on 17 O values of nitrate. A significant increase in stream nitrate co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 75 publications
4
40
0
Order By: Relevance
“…In 5 addition to these traditional isotopes, 17 O-excess (Δ 17 O; the definition will be presented in section 1.2) of nitrate has been used as an additional, more robust tracer for unprocessed NO 3 − atm (nitrate that had been supplied via atmospheric deposition and have survived the biological processing of nitrate, such as assimilation and denitrification, within surface ecosystems) in stream water in recent years (Bourgeois et al, 2018;Michalski et al, 2004;Riha et al, 2014;Sabo et al, 2016;Tsunogai 10 et al, 2010;Tsunogai et al, 2014;Tsunogai et al, 2016). By determining both concentration and the 17 O-excess of stream nitrate, we can quantify unprocessed NO 3 − atm in stream water accurately and precisely.…”
Section: Stream Nitrate Being Exported From Forested Watersheds 10mentioning
confidence: 99%
See 4 more Smart Citations
“…In 5 addition to these traditional isotopes, 17 O-excess (Δ 17 O; the definition will be presented in section 1.2) of nitrate has been used as an additional, more robust tracer for unprocessed NO 3 − atm (nitrate that had been supplied via atmospheric deposition and have survived the biological processing of nitrate, such as assimilation and denitrification, within surface ecosystems) in stream water in recent years (Bourgeois et al, 2018;Michalski et al, 2004;Riha et al, 2014;Sabo et al, 2016;Tsunogai 10 et al, 2010;Tsunogai et al, 2014;Tsunogai et al, 2016). By determining both concentration and the 17 O-excess of stream nitrate, we can quantify unprocessed NO 3 − atm in stream water accurately and precisely.…”
Section: Stream Nitrate Being Exported From Forested Watersheds 10mentioning
confidence: 99%
“…By determining both concentration and the 17 O-excess of stream nitrate, we can quantify unprocessed NO 3 − atm in stream water accurately and precisely. Recent studies on nitrate including unprocessed NO 3 − atm exported from forested catchments via streams during base flow period have revealed that the export flux of unprocessed NO 3 − atm increases in accordance with increases in the stream nitrate concentration (Rose et al, 15 2015a; Rose et al, 2015b;Tsunogai et al, 2014). These results implied that unprocessed NO 3 − atm exported from forested catchments can be used as a tracer to identify the biological processing of nitrate in each catchment area and to clarify the processes regulating nitrate concentrations in stream water.…”
Section: Stream Nitrate Being Exported From Forested Watersheds 10mentioning
confidence: 99%
See 3 more Smart Citations